2001
DOI: 10.1007/bf03019811
|View full text |Cite
|
Sign up to set email alerts
|

High concentration sevoflurane induction of anesthesia accelerates onset of vecuronium neuromuscular blockade

Abstract: 34GENERAL ANESTHESIA Purpose: To investigate neuromuscular block using accelography after administration of vecuronium under sevoflurane 8% induction and maintenance with sevoflurane 2% in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Ahmed et al [ 17 ] also reported that an increase in sevoflurane exposure time did not shorten the time to maximum block. However, Yamaguchi et al [ 18 ] reported that 8 % sevoflurane induction accelerates the onset of the vecuronium neuromuscular blockade. They found that the maximum block in the 8 % sevoflurane group was shorter than that in the propofol/fentanyl group and the N 2 O/2 % sevoflurane group (139 ± 35 s, 193 ± 35 s, and 188 ± 47 s, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed et al [ 17 ] also reported that an increase in sevoflurane exposure time did not shorten the time to maximum block. However, Yamaguchi et al [ 18 ] reported that 8 % sevoflurane induction accelerates the onset of the vecuronium neuromuscular blockade. They found that the maximum block in the 8 % sevoflurane group was shorter than that in the propofol/fentanyl group and the N 2 O/2 % sevoflurane group (139 ± 35 s, 193 ± 35 s, and 188 ± 47 s, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of sevoflurane on the onset of neuromuscularblocking drugs have been studied only at adductor pollicis muscles. Yamaguchi et al evaluated the effects of inhalation of sevoflurane as an induction agent on the onset time of neuromuscular-blocking drugs [9]. They reported that induction with 8% sevoflurane accelerated the onset time of 0.1 mg kg −1 vecuronium compared with induction with propofol [9].…”
Section: Discussionmentioning
confidence: 99%
“…Yamaguchi et al evaluated the effects of inhalation of sevoflurane as an induction agent on the onset time of neuromuscular-blocking drugs [9]. They reported that induction with 8% sevoflurane accelerated the onset time of 0.1 mg kg −1 vecuronium compared with induction with propofol [9]. Conversely, using intravenous agents for the induction of general anesthesia, several authors reported that the onset time of nondepolarizing neuromuscular-blocking drugs was not shortened by sevoflurane at concentrations <2%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Compared to the conventional inhalation induction technique using a gradual increase of concentration, a high concentration sevoflurane induction produced a rapid induction and reduced adverse effects. 4 Furthermore, sevoflurane induction provided additional advantages such as good cardiovascular stability, 3,6,7 smooth transition between induction and maintenance, 6,8 and rapid onset of non-depolarizing muscle relaxant 9 compared with iv induction.…”
mentioning
confidence: 99%